Archaeological investigations on Cape Ljubljana in Ljubač near Zadar (In situ, 2024)
The paper presents the results of archaeological investigations carried out as part of the fieldwork practice for archaeology students during the year 2023 at the Ljubljana site in Ljubač.
Keywords: Ljubljana; Ljubač; Middle Ages; Modern Period; St. Marcella; St. Mary